SIMULAC ~AO AB INITIO DE BASES NITROGENADAS INTERAGINDO COM NANOFITAS DE GRAFENO E SILICENO: PARAMETRIZAC ~AO E COMPARATIVO NOS DIFERENTES MATERIAIS - Martins, Mirkos Ortiz (2016)
In this thesis is studied the interaction between the nitrogenous bases, adenine, cytosine, guanine and thymine with two nanostructures: the graphene and silicene nanoribbons through ab initio calculations based on DFT (Density Functional Theory) using the SIESTA (Spanish Initiative for Electronic Simulations with Thousands of Atoms) software. Prior to implementing the software to simulate the behavior at the atomic level of molecules all feature and variants was studied, for computer modeling and simulation; which applications using nanostructures and the best spatial con guration for construction of an initial parameter simulation. The nitrogenous bases as main constitution of the genetic code component, in the form of a double trainer strand of DNA, is the point of interest of this work, along with their behavior when the interaction, by positioning the walking distance - with nanoribbons graphene and silicene. The simulation of the nitrogenous bases and nanoribbons initially obey perpendicular position with the atoms of forming hydrogen bonds in DNA, pointing to the nanostructures. It was calculated, at the end of the simulations, the removal of nitrogenous bases of its current initial position, the di erence in the values of total energy and charge transfer. It has been shown that the interaction energy between nitrogenous bases and graphene nanoribbon are thinner than those found for the interaction with the silicene nanoribbon. When the nitrogenous bases are placed parallel to nanoribbons (both of graphene as silicene) they present chemical bonds, while when they are arranged perpendicularly to the surface of the material, they deviate in the course of its transverse path. It also follows that the silicene nanoribbon is more stable in the adsorption energy than nanoribbon graphene and the interaction of the bases is the energy bands that change xiii subtly, with respect of the gap values. For the graphene nanoribbon, the changes are associated with the position of the Fermi level. These results show, in an original way, di erent con gurations for the nitrogeneous basis on one dimensional carbon and silicon materials.